Phenotype and envelope gene diversity of nef-deleted HIV-1 isolated from long-term survivors infected from a single source - Sullivan John S (Virology Journal, 2007)
Abstract Background The Sydney blood bank cohort (SBBC) of long-term survivors consists of multiple individuals infected with attenuated, nef-deleted variants of human immunodeficiency virus type 1 (HIV-1) acquired from a single source. Long-term prospective studies have demonstrated that the SBBC now comprises slow progressors (SP) as well as long-term nonprogressors (LTNP). Convergent evolution of nef sequences in SBBC SP and LTNP indicates the in vivo pathogenicity of HIV-1 in SBBC members is dictated by factors other than nef. To better understand mechanisms underlying the pathogenicity of nef-deleted HIV-1, we examined the phenotype and env sequence diversity of sequentially isolated viruses (n = 2) from 3 SBBC members. Results The viruses characterized here were isolated from two SP spanning a three or six year period during progressive HIV-1 infection (subjects D36 and C98, respectively) and from a LTNP spanning a two year period during asymptomatic, nonprogressive infection (subject C18). Both isolates from D36 were R5X4 phenotype and, compared to control HIV-1 strains, replicated to low levels in peripheral blood mononuclear cells (PBMC). In contrast, both isolates from C98 and C18 were CCR5-restricted. Both viruses isolated from C98 replicated to barely detectable levels in PBMC, whereas both viruses isolated from C18 replicated to low levels, similar to those isolated from D36. Analysis of env by V1V2 and V3 heteroduplex tracking assay, V1V2 length polymorphisms, sequencing and phylogenetic analysis showed distinct intra- and inter-patient env evolution. Conclusion Independent evolution of env despite convergent evolution of nef may contribute to the in vivo pathogenicity of nef-deleted HIV-1 in SBBC members, which may not necessarily be associated with changes in replication capacity or viral coreceptor specificity.